“But it did happen”: Sound as Deep Narrative in P.T. Anderson’s Magnolia (1999) - Hawksley, Theodora (The journal of religion and film, 2009)
This paper explores how sound is used in P. T. Anderson’s Magnolia to convey the deep narrative of the film. Through analysing how sound is employed to suggest meaning, form associations and create narrative coherence for the viewer, I argue that sound conveys an underlying narrative of redemption which climaxes apocalyptically in the rain of frogs. I then read this aspect of the film theologically through Barth, by drawing comparisons between Magnolia’s claim to be ‘strange but true’ and the church’s creedal stake in strange stories which claim universal meaning and redemptive significance. By looking at Magnolia’s use of sound to convey narrative, lessons are drawn out for the church in terms of how it might humbly perceive but resolutely proclaim narratives of universal significance in the climate of postmodernity.